Prevalence of indications for adult hepatitis A vaccination among hepatitis A outbreak-associated cases, Three US States, 2016–2019. Issue 44 (22nd October 2021) - Hofmeister, Megan G.; Weng, Mark K.; Thoroughman, Douglas; Thomasson, Erica D.; McBee, Shannon; Foster, Monique A.; Collins, Jim; Burkholder, Cole; Augustine, Ryan J.; Spradling, Philip R.
Abstract: Background: Safe and effective hepatitis A vaccines have been recommended in the United States for at-risk adults since 1996; however, adult vaccination coverage is low. Methods: Among a random sample of adult outbreak-associated hepatitis A cases from three states that were heavily affected by person-to-person hepatitis A outbreaks, we assessed the presence of documented Advisory Committee on Immunization Practices (ACIP) indications for hepatitis A vaccination, hepatitis A vaccination status, and whether cases that were epidemiologically linked to an outbreak-associated hepatitis A case had received postexposure prophylaxis (PEP). Results: Overall, 74.1% of cases had a documented ACIP indication for hepatitis A vaccination. Fewer than 20% of epidemiologically linked cases received PEP. Conclusions: Efforts are needed to increase provider awareness of and adherence to ACIP childhood and adult hepatitis A vaccination and PEP recommendations in order to stop the current person-to-person hepatitis A outbreaks and prevent similar outbreaks in the future.